Preliminary epi-diode characterization for HDR brachytherapy quality assurance. (January 2019) - Romanyukha, A A; Carrara, M; Cutajar, D; Petasecca, M; Fuduli, I; Al-Salmani, T; Lerch, M.; Perevertaylo, V.; Mazzeo, D; Cerrotta, A; Fallai, C; Pignoli, E; et al.
Abstract: High Dose Rate vaginal brachytherapy for endometrial cancer has evolved from simple single-channel (i.e. cylindrical applicator) deliveries to treatments involving several channels (i.e. multichannel applicator) for the radiotherapy source to dwell, increasing the complexity of the dose distribution, and allowing more space for potential errors. For this reason real-time treatment verification has gained a greater importance than ever before, and more methods need to be developed in order to provide assurance that the dose delivery has been carried out as intended by the hospital staff. P-type silicon epi diodes have been designed at the Centre for Medical Radiation Physics (CMRP) in Australia to suit the specific needs of HDR BT, and characterized in the clinical BT facility of the Fondazione IRCCS (INT) in Italy. They have shown great potential for BT treatment verification in real time due to their radiation hardness, dose rate independence, flexibility in physical design, and ability to monitor the treatment at a 1-kHz readout frequency. Their dynamic range has been determined as ±17 to ±20 mm and dwell time calculation accuracy of > 0.1 s has been shown. If placed on the same longitudinal plane of a treatment accessory, these detectors would enable coverage of about 40 mm for source position and dwell time tracking. Respective detector positioning at (0, +3, −3 mm) would extend this range to 45-50 mm, depending on the catheter location, proving to be sufficient for the majority of treatment cases. Further studies are encouraged to develop diodes with a wider dynamic range.